2002
DOI: 10.1177/0143034302234007
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment and Strain among Domestic and International Student Sojourners

Abstract: Every year, a growing number of students leave their home environments and relocate to study at universities abroad. Relocation, however, can be a challenging and stressful experience. This longitudinal study surveyed 294 international and domestic student sojourners to examine and compare their adjustment and distress or strain responses during the first six months of their entry into a medium-sized, mid-western US state university. The findings revealed that international student sojourners, compared to dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(207 citation statements)
references
References 21 publications
16
177
2
3
Order By: Relevance
“…Zhang and Brunton (2007) found that 55% of their sample of Chinese international students in New Zealand were unhappy with their opportunities to make friendships with locals, and 71% reported that they would like to have more local friends. In other studies, international students have reported perceptions of less social support than domestic students (Hechanova-Alampay, Beehr, Christiansen, & Van Horn, 2002;Khawaja & Dempsey, 2008), and more loneliness and homesickness (Parr & Bradley, 1991;Rajapaksa & Dundes, 2002). Contrary to these findings, Klomegah (2006) found no significant difference in levels of feeling alienated between domestic and international students in the U.S.A.…”
Section: Sociocultural Stressorsmentioning
confidence: 89%
“…Zhang and Brunton (2007) found that 55% of their sample of Chinese international students in New Zealand were unhappy with their opportunities to make friendships with locals, and 71% reported that they would like to have more local friends. In other studies, international students have reported perceptions of less social support than domestic students (Hechanova-Alampay, Beehr, Christiansen, & Van Horn, 2002;Khawaja & Dempsey, 2008), and more loneliness and homesickness (Parr & Bradley, 1991;Rajapaksa & Dundes, 2002). Contrary to these findings, Klomegah (2006) found no significant difference in levels of feeling alienated between domestic and international students in the U.S.A.…”
Section: Sociocultural Stressorsmentioning
confidence: 89%
“…These results confirm the results of previous research studies claiming that interaction with host nationals can be highly beneficial in the cultural adjustment process (Caligiuri et al, 1998;Hechanova-Alampay et al, 2002;Hendrickson et al, 2010;Li & Gasser, 2005;Ward & Rana-Deuba, 2000). This knowledge can encourage missionaries to be intentional about building relationships with host nationals in their country of service Additionally, the results of this study showed the importance of stability in the missionary's relationship with God.…”
Section: Recommendations For Missionariessupporting
confidence: 90%
“…Ten international EAL students were recruited from two social science faculties, nine of whom were of Chinese ethnicity (Table 1). Data collection was carried out during students' initial academic semester which was likely to present substantial help-seeking or brokering activity, since it was a period that presented the greatest adjustment challenges for students (Hechanova-Alampay, Beehr, Christiansen, & Van Horn, 2002;Ward, Okura, Kennedy, & Kojima, 1998). In view of the relatively short timeframe, I used focused ethnography to examine the specific phenomenon of brokering among a particular group of students (Higginbottom, Pillay, & Boadu, 2013;Knoblauch, 2005).…”
Section: Methodsmentioning
confidence: 99%